Experimental investigations of air and liquid injection by venturi tubes - Ozkan, Fahri; Ozturk, Mualla; Baylar, Ahmet (Blackwell Publishing, 2006)
The venturi system creates a pressure differential that forms a vacuum. As water flows through the tapered venturi orifice, a rapid change in velocity occurs. This velocity change creates a reduced pressure (vacuum), which draws air and liquid to be injected into the system. The air and liquid injection rates vary with the pressure differential across the venturi. Typical applications of venturi tubes are for injecting fertilizers, chemicals, ozone gas, air or oxygen into pressurized water systems. In this paper, experimental studies were conducted to investigate the effects of inlet and throat diameters of the venturi tube, pipe length downstream of the venturi tube, diameter of the suction pipe at the throat portion of the venturi tube, angle of the pipe downstream of the venturi tube, flow velocity at the inlet portion of the venturi tube and density and viscosity of the liquid injected into the venturi tube on air and liquid injection rate. It was observed from the results that venturi tubes had high air and liquid injection efficiencies.
Keywords: aeration; chemigation; dissolved oxygen; injection; irrigation; venturi